“Agulha no Palheiro”: Modelos de Distribuição Geográfica da Cuíca D’água (chironectes Minimus) Através do Tempo - Bretas, Diego de Souza (2021)
The water opossum (Chironectes minimus) is unique from a morphological and ecological standpoint, being the only marsupial really adapted for a semiaquatic lifestyle. Morphologically, it is a very peculiar animal, which presents a series of adaptations similar to those found in otters. Its conservation status varies, depending on the spatial scale observed and, due to its lifestyle, it ends up being underrepresented in inventories based on traditional capture techniques. As a consequence, it is poorly understood in terms of its basic ecological aspects. Historically, its geographic distribution is not uniform, generating inconsistencies about its classification. It is well known that it is essential to understand the distribution of any given species as an essential step on the development of efficient strategies for the conservation of biodiversity, both currently and in future environmental scenarios. Modern tools, such as Species Distribution Models, are able to predict the potential distribution of various taxa, based on occurrence records and environmental variables relevant to their persistence. In this context, this study estimated the geographic distribution of current watershed and in different future scenarios, from the elaboration of species distribution models, using MaxEnt 3.4.1 and RStudio software. We used 480 occurrence records and ten bioclimatic variables in the elaboration of both current distribution models and in different future environmental scenarios. Based on the generated models, we can see the expansion of the potential geographic distribution of C. minimus currently known by the IUCN, reinforcing the need for its update. Regarding the geographic distribution of the species in the future, we could observe the contraction of environmentally suitable areas according to the increase on the intensity of global warming effects. Large portions of environmentally suitable areas for its persistence in the equatorial zone are lost, leaving only small isolated patches between South and Central America, in the Guianas region and in the southern and southeastern portion of Brazil. Some regions remained stable in relation to the probability of occurrence of the species, which may represent an indication of greater success in choosing future locations for studies involving C. minimus. The compilation of the new occurrence records in a complete database allowed us to elaborate more accurate distribution models, filling some important gaps in the current geographic distribution of the water opossum. Regarding the type of geographic distribution presented by the species, our results suggest that, although some gaps exist, the species has a continuous distribution.